Where's my mummy? - Crimi, Carolyn; Manders, John (New York : Scholastic, 2009)
One deep, dark night, as all of the monsters are preparing for bed, Little Baby Mummy bravely searches for his mother until he sees a truly terrifying creature.
"This edition is available for distribution only through the school market"--Cover verso.
Originally published: Cambridge, Mass. : Candlewick Press, 2008.
AD500L
Decoding demand: 68 (high) Semantic demand: 67 (high) Syntactic demand: 71 (high) Structure demand: 71 (high)
Accelerated Reader AR
Keywords: Mummies -- Juvenile fiction; Mother and child -- Juvenile fiction; Bedtime -- Juvenile fiction; Fear -- Juvenile fiction; Monsters -- Juvenile fiction